2018
DOI: 10.3390/nu10111810
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Comparison of Nutritional Supplement Use, Knowledge, and Attitudes in Medical and Non-Medical Students in China

Abstract: The objective of this study is to investigate and compare the prevalence, knowledge, and attitudes of Chinese university students with respect to nutritional supplements. We conducted a cross-sectional study in several universities around China from January to December 2017, and enrolled a total of 8752 students. Of these, 4252 were medical students and 4500 were non-medical students. The use of nutritional supplements was reported by 58.9% in universities students, with a higher rate for medical students as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 67 publications
3
13
0
1
Order By: Relevance
“…In addition, this study revealed that nutrition knowledge was higher in participants from medical colleges. This result was consistent with other studies among university students (medical and non-medical) (20,21) . The effect of the intervention on knowledge scores differed significantly across colleges.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, this study revealed that nutrition knowledge was higher in participants from medical colleges. This result was consistent with other studies among university students (medical and non-medical) (20,21) . The effect of the intervention on knowledge scores differed significantly across colleges.…”
Section: Discussionsupporting
confidence: 94%
“…Sus funciones son complementar la insuficiencia de nutrientes, prevenir deficiencias nutricionales y reducir el riesgo de ciertas enfermedades crónicas no transmisibles. 15 Las definiciones anteriormente mencionadas presentan limitaciones contextuales, ya que en una declaración en consenso por parte de miembros del Comité Olímpico Internacional (COI) se sugiere que un suplemento alimenticio es un alimento, componente alimenticio, nutriente o compuesto no alimenticio que es ingerido a propósito, adicional a la dieta habitualmente consumida, con el objetivo de conseguir un beneficio específico de salud o rendimiento. Las diversas formas en las que se presentan los suplementos alimenticios incluyen: a) alimentos funcionales, alimentos enriquecidos con nutrientes adicionales o componentes fuera de su composición nutrimental típica; b) alimentos formulados y alimentos deportivos, productos que proporcionan energía y nutrientes de una forma más conveniente que los alimentos para apoyo nutricional general (p.…”
Section: Suplementos Alimenticiosunclassified
“…Moreover, medical students more commonly used single-use masks and wore face protection for longer periods of time [25]. This is not surprising, as the differences in health-related attitudes and behaviors between medical and non-medical students have been previously documented [26][27][28]. The criterion that non-medical students complied significantly better with was the disposure of single-use masks after their use at work.…”
Section: Discussionmentioning
confidence: 89%